NIEMIECKA SCENA POLITYCZNA PO WYBORACH W 1994 I 1998 ROKU. KIERUNKI EWOLUCJI - Fłakowski, Jarosław (In Gremium. Studies in History, Culture and Politics, 2010)
GERMAN POLITICAL SCENE FOLLOWING THE 1994 AND 1998 ELECTIONS. THE DIRECTIONS OF THE EVOLUTION This article is devoted to the presentation of the dynamism of changes observable as a result of the struggle for power in the German political system during Bundestag deputies elections in the years 1994 and 1998. In order to describe precisely the regularities of the conduct of election campaigns in the Federal Republic of Germany, the article presents some definitions of the elements which set the research ’frames’ of the German political scenes. ·The author discusses the Bundestag election system, the idea of a party and the party system as well as basic concepts of political marketing. Part two describes German political parties including their activities and programmes after 1989. The following part contains information concerning the course of political campaigns conducted prior to the 1994 and 1998 elections. Parr four includes an analysis of power arrangement in Bundestag observable after the above-mcnrioned elections. The last part of the article presents the classification of German party system in the particular research period. The article has been enriched with cham including statistical data which facilitate the visualisation of the discusses subject. The considerations included in the article do not cover the subject entirely, however they shall become the outset of wider research on the dynamism of changes occurring within the German political scene after the unification of the Federal Republic of Germany and the German Democratic Republic.